1,2-Bis(phenylsulfonyl)ethylene (BPSE): A Potent Radical C2 Synthon Available in the Radical and Electron-Transfer-Based Organic Synthesis - Sumino, Shuhei; Ryu, Ilhyong; Robert, Frédéric; Landais, Yannick (Synthesis, 2024)
In this Short Review, we discuss radical reactions using 1,2-bis(phenylsulfonyl)ethylene (BPSE), which has drawn significant attention as a versatile building block for (phenylsulfonyl)ethenylation. Regardless of its E or Z form, BPSE exhibits reliable reactivity towards the attack of alkyl and aryl radicals in order to function as a reliable radical C2 synthon.1 Introduction2 Use in Radical Chain Reactions3 Use in Reactions Utilizing an Electron-Transfer Process4 Use in Radical-Based C–H Alkenylation5 Conclusion
Keywords: 1,2-bis(phenylsulfonyl)ethylene; radical C2 synthon; β-scission; phenylsulfonyl radical; radical alkenylation